GROWING POPULARITY OF MICE TOURISM IN UZBEKISTAN AND FOREIGN COUNTRIES - Khalilova Gulnoza Nurullo qizi (Web of Journals Publishing, 2024)
This article presents the procedure for organizing MICE tourism events in our country, competition in the MICE field, information on the difficulties encountered by enterprises operating in this field in the process of receiving foreign guests, and opinions and comments on foreign experience in the development of this field.
Keywords: MICE tourism, competition, tourist companies, business meetings, tour services.